"Big Challenges" and Regional Technical University: Values and Actions - R. V. Aginey; O. I. Belyaeva (Moscow Polytechnic University, 2020)
The system of "big challenges" formulated in the "Strategy of scientific and technological development of the Russian Federation" is projected by the authors on the model of regional technical university. This projection is mediated by the concretization of the system of big challenges with regard to the social and economic development of a separate region of Russia (Komi Republic). An attempt to explicate the value basis of the system of "big calls" has been undertaken. The article considers the methods of embedding the value axiomatics of "big challenges" into the value profile of university organizational culture. There is a distinction between civilization and globalist paradigms of Russia positioning, as well as a distinction between well-being and security as two strategies of values generalization. In defining the development strategy of the regional technical university in the context of "big challenges," the modus of values and the modus of action are highlighted. According to the modus of values, the expediency of focus on the "second scenario" of development provided for in the "Strategy of scientific and technological development of the Russian Federation" (optimistic) is justified. The authors emphasize the possibility of effective reflection of the value axiomatics of "big challenges" by the university community due to a special technology of monitoring and adjusting the university organizational culture referred to as "value-competence parallelepiped".